Duration of Immunity in Cutaneous Leishmaniasis - Rasulova I.A; Khamdamov A.B (Periodica Journal, 2022)
This article presents the results of studies of the state of immunity in blood serum and affected areas of the skin in patients with cutaneous leishmaniasis in comparison with the indicators of healthy individuals.
Keywords: individuals; comparison; indicators; blood